PENERAPAN ALAT FOTO PASTEURISASI-UV UNTUK MENINGKATKAN MUTU PRODUKSI SELAI DAN JAM BUAH JAMBU METE DI DESA GAPURA GAYAM, TUKLUK, NGADIROJO, WONOGIRI - Purnomo, Abdullah Ridhwan; Intaniasari, Adisti Putri; Kristiana, Winda (Program Kreativitas Mahasiswa - Teknologi, 2013)
During the cashew fruit growers only use cashews to be sold and processed into cashew nuts. While the fruit is not utilized optimally because the cashew fruit flavors tastes not good and can cause itching. In the Winton area are SMEs that develop the production of jam and hours. Constraints faced by SMEs are the tools which they use tools conventional pasteurization, the heat treatment of the jam and hours performed over the fire in a saucepan and cook until the temperature of 800C which is known to jam thermometer dipped into being heated and heating times of uncertainty, the method does not necessarily guarantee the quality of the jam, so pasteurization is developing automated tools. Tool automatically pasteurization as a means substitution of conventional pasteurization methods, equipped with a thermostat temperature, stirrer and timer and also ultra violet light. The tool is then tested to provide heat treatment on the jam clock with temperature and 610C for 30 minutes. It is expected that with this tool pasteurization process can take place with the first stage of which will boost the production capacity of 750 bottles / day of initial capacity of 100 bottles / day. Increased capacity followed by an increase in profit, when the production capacity of 100 bottles / day with a selling price of butter and jam USD $ 3000.00 per bottle, SMEs only make a profit of Rp 300,000.00 / day, while after reaching production capacity of 500 bottles / day at a price the same sales profit reached Rp 2,250,000.00 gained / day. Also expected product will be more hygienic and durable and able to reduce costs during the production process. So the cashew fruit can be processed into jams and soon to avoid congested hour of raw materials.